Život v pražském klášteře sv. Jiří ve středověku - Pacovský, Karel (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2023)
This dissertation focuses on the community of Benedictine nuns at St. George's Church in Prague Castle from its foundation around 970 to the 16th century. It is based on a detailed study of primary sources (especially surviving monastic charters, manuscripts, but also records of church administration and other extra-monastic references) and takes into account the results and approaches of contemporary monastic research. Thus, the doctoral thesis revises existing knowledge and traditional clichés, opens new questions and seeks answers to old ones (e. g. concerning convent's Benedictine observance, Latin literacy of the nuns, the enclosure, and authority over the abbey). It is the first scholarly work to examine in detail the number and origins of the nuns, their education, kinship ties, contacts, and the spatial framework that determined their everyday life. It also traces the wider staff of their church and analyses in detail the major conflicts that influenced the development of the convent.
Keywords: Middle Ages|Prague Castle|Benedictine nuns|St. George's Convent in Prague|St. George's canons|medieval monasticism|medieval Latin|Latin literacy|women's history|Mlada|St. Ludmila|enclosure|Czech Reformation; středověk|Pražský hrad|benediktinky|svatojiřský klášter|svatojiřští kanovníci|středověké mnišství|středověká latina|latinská vzdělanost|dějiny žen|Mlada|sv. Ludmila|klauzura|česká reformace